Method for rapidly synthesizing self-supporting high-entropy alloy difunctional electrocatalyst by Joule heat

Through Joule thermal synthesis of self-supported high-entropy alloy nanoparticle electrocatalyst, the problems of high cost and insufficient stability of precious metal catalysts are solved, and high-efficiency electrochemical water decomposition under alkaline and neutral conditions are achieved, with excellent dual-function electrical Catalytic performance and low production costs.

CN119465285APending Publication Date: 2025-02-18QINGDAO UNIV OF SCI & TECH
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411589898.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

In the prior art, the noble metal-based compound catalyst has high cost and insufficient stability, making it difficult to achieve efficient water decomposition in alkaline electrochemical water decomposition, especially at high current density.

Method used

The self-supported high-entropy alloy nanoparticles were rapidly synthesized by Joule heat to form a FeCuRu@Ni1Co1-TPA high-entropy alloy electrocatalyst for electrochemical water decomposition. The method includes pretreating foam nickel as a support, synthesizing and coating a high-entropy alloy precursor, followed by Joule thermal calcination to form a high-entropy alloy nanoparticle electrocatalyst.

Benefits of technology

Under alkaline and neutral conditions, FeCuRu@Ni1Co1-TPA high-entropy alloy electrocatalyst shows excellent dual-function electrocatalytic performance, can achieve high current density at lower overpotentials, suitable for electrochemical water decomposition, and reduce The cost of the catalyst and the stability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005125306550000011
    Figure HDA0005125306550000011
  • Figure HDA0005125306550000012
    Figure HDA0005125306550000012
  • Figure HDA0005125306550000013
    Figure HDA0005125306550000013
Patent Text Reader

Abstract

The invention belongs to the field of catalyst preparation, and provides a preparation method for rapidly synthesizing a self-supporting high-entropy alloy difunctional electrocatalyst through Joule heat. The prepared FeCuRu-coated Ni1Co1-TPA is benefited from rich active sites, and the high conductivity of effective electron transfer and transmission is achieved. The catalyst shows excellent HER and OER catalytic performance under an alkaline condition, and the current density of 500mA cm <-2 > can be realized by only needing overpotentials of 120mV and 350mV, which is superior to those of a standard noble metal catalyst Pt / C and RuO2. In addition, when the composite material is used as a bifunctional electrocatalyst for electrolyzing water, the composite material shows excellent catalytic activity for electrolyzing water. The method has important significance for realizing the social renewable development target and developing clean and sustainable energy resources to replace fossil fuel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalyst preparation, and in particular to the Joule heat rapid synthesis of a self-supporting high entropy alloy bifunctional electrocatalyst for efficient water decomposition. Technical Background

[0002] The growth of global energy demand and environmental degradation have led to the rapid consumption of fossil fuels, which has prompted the world to urgently search for sustainable energy. Hydrogen is considered to be one of the most promising energy carriers to replace or even substitute fossil fuels due to its high energy density and zero carbon emissions. Among them, electrochemical water splitting has attracted widespread attention as an effective way to achieve large-scale production of hydrogen fuel. However, the slow cathode hydrogen evolution reaction (HER) and anode oxygen evolution reaction (OER) have hindered the development of water splitting. In order to solve the slow kinetics of the cathode and anode and avoid complex multi-electron reaction pathways, it is urgent to design and synthesize a bifunctional HER and OER electrocatalyst that can accelerate the reaction rate while reducing the overpotential.

[0003] Currently, noble metal-based compounds such as Pt / C and RuO2 / IrO2 are considered as benchmark catalysts for HER and OER, respectively. However, the high cost and insufficient stability of noble metals have greatly hindered the commercial application of alkaline electrochemical water splitting. In addition, since most commercially available electrolyzers are of alkaline type, while HER catalysts show excellent performance in acidic media, OER catalysts are more favorable in alkaline environments. Therefore, matching two incompatible catalysts may lead to a decrease in the efficiency of alkaline electrochemical water splitting. In recent years, researchers have made great efforts to design the synthesis of catalysts by using low-cost and resource-abundant elements. However, high overpotential, poor stability and unsatisfactory efficiency, especially at high current density, remain the main obstacles to the further development of non-noble metal electrocatalysts. Therefore, it is urgent to develop high-performance, durable and high-current-density bifunctional alkaline catalysts for HER and OER in electrochemical water splitting.

[0004] Among the many electrocatalyst synthesis methods, alloying has been shown to be of great significance in adjusting the electronic structure and the adsorption and desorption free energy of intermediates in the reaction process. This method can not only accelerate the catalytic process but also reduce the catalyst cost. However, the synthesis of nano-alloyed catalysts remains a challenge, which usually involves complex synthesis steps and harsh calcination conditions. Therefore, it is particularly important to design and synthesize a fast, low-cost and self-supporting bifunctional HER and OER electrocatalyst. Summary of the invention

[0005] In order to solve the above problems and achieve social sustainable development goals and carbon neutrality plans, the present invention provides a method for quickly preparing self-supporting high entropy alloy nanoparticles through Joule heat technology, and using them as a bifunctional electrocatalyst for water electrolysis. This electrocatalyst has excellent electrocatalytic activity under alkaline and neutral conditions.

[0006] To achieve the above object, the present invention adopts the following technical solution:

[0007] The first aspect of the present invention provides a method for rapidly synthesizing a bifunctional self-supporting high entropy alloy nanoparticle electrocatalyst using Joule heat, comprising the following steps:

[0008] (1) Pretreatment of the self-supporting carrier: pretreatment of the nickel foam with acetone, ethanol, and hydrochloric acid;

[0009] (2) Synthesis of high entropy alloy precursor: 2-amino-terephthalic acid, sodium hydroxide, and two metal chlorides of Co and Ni are uniformly dissolved in an ethanol solvent and subjected to an oil bath, followed by centrifugal washing to obtain Ni1Co1-TPA;

[0010] (3) Further adsorption of metal salts: the above product Ni1Co1-TPA is further dispersed into an aqueous solution containing three metal salts of Fe, Cu and Ru for adsorption under stirring at room temperature;

[0011] (4) Precursor washing and drying: The reactant obtained in step (3) is centrifuged, and the obtained product is washed three times with ethanol and deionized water respectively, and the solid mixture is placed in a vacuum drying oven for drying;

[0012] (5) Preparation of self-supporting electrocatalyst: preparing the catalyst powder obtained in step (4) into a uniformly dispersed liquid droplet and applying it to the pretreated nickel foam described in step (1), and drying to obtain a nickel foam coated with a high entropy alloy precursor;

[0013] (6) Joule heating of the electrocatalyst: The nickel foam coated with the high entropy alloy precursor is subjected to Joule heating in an argon atmosphere to obtain the desired sample FeCuRu@Ni1Co1-TPA.

[0014] The present invention forms FeCoNiCuRu high entropy alloy nanoparticle electrocatalyst by Joule heat treatment of nickel foam coated with five metal precursors. When it is used as an electrode to test hydrogen evolution (HER) and oxygen evolution (OER) performance, only 120mV and 350mV overpotentials are required under alkaline conditions to achieve 500mA cm -2 The current density reaches 50 mA cm under neutral conditions. -2The current density only requires 83mV and 280mV overpotential, and has excellent HER and OER performance under alkaline and neutral conditions. When used for two-electrode water electrolysis, FeCuRu@Ni1Co1-TPA high entropy alloy nanoparticles can show excellent electrocatalytic performance as anode and cathode, and can achieve 100mA cm at only 1.58V in alkaline conditions. -2 of current density.

[0015] The second aspect of the present invention provides a bifunctional electrocatalyst prepared by the above method.

[0016] The third aspect of the present invention provides the use of the above-mentioned bifunctional electrocatalyst in water decomposition.

[0017] Beneficial effects of the present invention:

[0018] (1) The present invention rapidly synthesizes FeCuRu@Ni1Co1-TPA high entropy alloy nanoparticles by Joule heating strategy. By changing the composition of the precursor, the structure and composition can be well regulated, so that an alloy structure of five metals with a uniform structure can be synthesized. The prepared FeCuRu@Ni1Co1-TPA high entropy alloy nanoparticle electrocatalyst shows excellent bifunctional electrocatalytic performance. Under alkaline conditions, only 120 and 350 mV overpotentials are required for HER and OER to reach 500 mA cm -2 When used as anode and cathode for overall water splitting, only 1.58 V is required to achieve 100 mA cm -2 These methods and insights will open new avenues for the rational design and exploration of low-cost and environmentally friendly bifunctional electrocatalysts.

[0019] (2) The preparation method of the present invention is simple, practical and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0021] Figure 1 is the SEM image of FeCuRu@Ni1Co1-TPA high entropy alloy powder;

[0022] Figure 2 is the TEM image of FeCuRu@Ni1Co1-TPA high entropy alloy powder;

[0023] Figure 3 It is the XRD structure diagram of FeCuRu@Ni1Co1-TPA high entropy alloy powder;

[0024] Figure 4 It is the linear sweep voltammogram of FeCuRu@Ni1Co1-TPA high entropy alloy, Pt / C, and Nafion / NF (electrocatalytic alkaline hydrogen evolution performance);

[0025] Figure 5 It is the linear sweep voltammogram of FeCuRu@Ni1Co1-TPA high entropy alloy, Pt / C, and Nafion / NF (electrocatalytic neutral hydrogen evolution performance);

[0026] Figure 6 It is the linear sweep voltammogram of FeCuRu@Ni1Co1-TPA high entropy alloy, RuO2, and Nafion / NF (electrocatalytic alkaline oxygen evolution performance);

[0027] Figure 7 It is the linear sweep voltammogram of FeCuRu@Ni1Co1-TPA high entropy alloy, RuO2, and Nafion / NF (electrocatalytic neutral oxygen evolution performance);

[0028] Figure 8 It is the linear sweep voltammogram (alkaline electrocatalytic water splitting performance) of FeCuRu@Ni1Co1-TPA high entropy alloy (+)||FeCuRu@Ni1Co1-TPA high entropy alloy (-), Pt / C(+)||RuO2(-) electrodes;

[0029] Fig. 9 It is the linear sweep voltammogram (neutral electrocatalytic water splitting performance) of FeCuRu@Ni1Co1-TPA high entropy alloy (+)||FeCuRu@Ni1Co1-TPA high entropy alloy (-), Pt / C(+)||RuO2(-) electrodes; Specific implementation methods

[0031] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments.

[0032] A method for rapidly synthesizing a bifunctional self-supporting high entropy alloy nanoparticle electrocatalyst using Joule heat, comprising:

[0033] Pretreating the self-supporting carrier nickel foam to obtain activated nickel foam;

[0034] Dissolve 2-amino-terephthalic acid, sodium hydroxide and two metal chlorides of Ni and Co uniformly in an ethanol solvent to obtain a mixed metal salt solution, and perform oil bath, centrifugal washing and drying to obtain Ni1Co1-TPA; further disperse Ni1Co1-TPA in an aqueous solution containing three metal salts of Fe, Cu and Ru, and perform stirring and absorption at room temperature, and separate, wash and vacuum dry to obtain a solid mixture powder FeCuRu@Ni1Co1-TPA;

[0035] The catalyst powder is prepared into uniformly dispersed droplets, applied to the activated nickel foam, and dried to obtain a nickel foam coated with a metal precursor;

[0036] The nickel foam coated with the metal precursor is subjected to Joule heating in a nitrogen atmosphere to obtain the desired sample.

[0037] In some embodiments, the bifunctional electrocatalyst is a FeCuRu@Ni1Co1-TPA high entropy alloy to synthesize an alloy structure with uniform five metals.

[0038] In some embodiments, the specific steps of pretreatment activation are: immersing the nickel foam in acetone for ultrasonic treatment for 0.5 to 1 hour, then ultrasonic treatment with ethanol for 0.5 to 1 hour to remove the acetone on the nickel foam, then ultrasonic treatment with 1M HCl for 0.5 to 1 hour, then rinsing with a large amount of deionized water, and then ultrasonic cleaning several times until neutral to improve its reactivity. Finally, drying at 60°C in a vacuum for 24 to 36 hours.

[0039] In the present application, there is no particular limitation on the specific types of Fe salts, Co salts, Ni salts, Cu salts, and Ru salts. In some embodiments, the Fe salt is FeCl3, the Co salt is CoCl2, the Ni salt is NiCl2, the Cu salt is CuCl2, and the Ru salt is RuCl3·xH2O to obtain better bifunctional electrocatalytic performance.

[0040] In some embodiments, the molar ratio of FeCl3, CoCl2, NiCl2, CuCl2, and RuCl3·xH2O is 0.5-2:0.5-2:0.5-2:0.5-2:0.5-2, so as to effectively regulate the structure and composition of the high entropy alloy catalyst by changing the ratio of the metal salts.

[0041] In some embodiments, in the mixed metal salt solution, the concentration of a single metal salt is 0.5-2 mmol so that the metal salt can be effectively dispersed in the ethanol solvent, which is convenient for subsequent distribution on nickel foam and synthesis of five metal alloys.

[0042] In some embodiments, the amount of 2-amino-terephthalic acid is 0.2-1 g, the amount of sodium hydroxide is 0.1-0.4 g, and the solvent ethanol is 50-250 mL.

[0043] In some embodiments, the specific conditions for uniformly dissolving the five metal chloride salts in the ethanol solvent are: ultrasonic treatment at room temperature for 1 to 3 hours to obtain a uniformly mixed solution.

[0044] In some embodiments, the specific conditions of the oil bath are: heating the oil bath to 50-100° C. in advance, and then heating the uniform mixed solution for 2-10 hours to obtain a precursor mixture.

[0045] In some embodiments, the specific conditions of the separation and washing are: separating the precursor mixture at 10,000 rpm for 5 minutes to remove the solvent, and then washing with ethanol and deionized water three times respectively.

[0046] In some embodiments, the catalyst powder is prepared into a uniform dispersion under the following conditions: 5 to 50 mg of the dried powder is dispersed in 1 mL of ethanol and ultrasonically dispersed for 0.5 to 2 h, 10 to 60 μL of Nafion solution is added, and ultrasonically dispersed for 0.5 to 2 h to form a uniform dispersion.

[0047] In some embodiments, the specific conditions for drop-coating the uniformly dispersed liquid onto the pretreated nickel foam are: cut the pretreated nickel foam into 1×2 cm, use a pipette to transfer the uniformly dispersed liquid and drop it onto the 1×1 cm nickel foam, irradiate and dry it with an infrared lamp, repeat this step to drop a total of 50 to 100 μL to form a metal precursor-coated nickel foam.

[0048] In some embodiments, Joule heating is performed at 900-2500° C. to rapidly synthesize an alloy structure having uniform five metals through a Joule heating strategy to obtain excellent bifunctional electrocatalytic performance.

[0049] The present invention will be further described in detail below in conjunction with specific embodiments. It should be noted that the specific embodiments are intended to explain the present invention rather than to limit it.

[0050] Example 1

[0051] FeCuRu@Ni1Co1-TPA high entropy alloy catalyst: First, the nickel foam was ultrasonically treated in acetone, ethanol and HCl (1M) for 0.5h for activation, and then ultrasonically cleaned and dried with a large amount of deionized water. 0.2g 2-amino-terephthalic acid and 0.1g sodium hydroxide were dispersed in 50mL ethanol and ultrasonically treated for 0.5h to disperse evenly. 0.5mmol NiCl2·6H2O and 0.5mmol CoCl2·6H2O were added in sequence and ultrasonically treated again for 0.5h to completely dissolve in 50mL ethanol. Then, the mixed solution was oil bathed at 50℃ for 2h, and Ni1Co1-TPA was obtained after separation, washing and vacuum drying. Ni1Co1-TPA was further dispersed in an aqueous solution containing three metal salts of 0.5mmol FeCl3·6H2O, 0.5mmol CuCl2 and 0.5mmol RuCl3 and stirred at room temperature for 2h. After separation, washing and vacuum drying, a solid mixture powder FeCuRu@Ni1Co1-TPA was obtained. After that, 5 mg of the obtained precursor powder was weighed and dispersed in 1 mL of ethanol for ultrasonic dispersion for 0.5 h, and then 10 μL of Nafion was added and ultrasonic dispersion was performed for another 0.5 h to form a uniform dispersion. 50 μL of the dispersion was dropped on a piece of activated nickel foam (1×1 cm) and dried by infrared lamp irradiation to obtain a nickel foam coated with a metal precursor. The nickel foam coated with a metal precursor was heated to 900°C in an argon atmosphere by Joule heating to obtain a FeCuRu@Ni1Co1-TPA high entropy alloy electrode.

[0052] Example 2

[0053] FeCuRu@Ni1Co1-TPA high entropy alloy catalyst: First, the nickel foam was ultrasonically treated in acetone, ethanol and HCl (1M) for 0.5h for activation, and then ultrasonically cleaned and dried with a large amount of deionized water. 0.5g 2-amino-terephthalic acid and 0.3g sodium hydroxide were dispersed in 100mL ethanol, ultrasonically treated for 0.5h to disperse evenly, 1mmol NiCl2·6H2O and 1mmol CoCl2·6H2O were added in sequence, and ultrasonically treated again for 1h to completely dissolve in 100mL ethanol. Then, the mixed solution was oil bathed at 80℃ for 5h, and Ni1Co1-TPA was obtained after separation, washing and vacuum drying. Ni1Co1-TPA was further dispersed in an aqueous solution containing 1mmol FeCl3·6H2O, 1mmol CuCl2 and 1mmol RuCl3 three metal salts and stirred at room temperature for 6h. After separation, washing and vacuum drying, a solid mixture powder FeCuRu@Ni1Co1-TPA was obtained. After that, 10 mg of the obtained precursor powder was weighed and dispersed in 1 mL of ethanol for ultrasonic dispersion for 0.5 h, and then 20 μL of Nafion was added and ultrasonic dispersion was performed for another 0.5 h to form a uniform dispersion. 70 μL of the dispersion was dropped on a piece of activated nickel foam (1×1 cm) and dried by infrared lamp irradiation to obtain a nickel foam coated with a metal precursor. The nickel foam coated with a metal precursor was heated to 1800°C in an argon atmosphere by Joule heating to obtain a FeCuRu@Ni1Co1-TPA high entropy alloy electrode.

[0054] Example 3

[0055] FeCuRu@Ni1Co1-TPA high entropy alloy catalyst: First, the nickel foam was ultrasonically treated in acetone, ethanol and HCl (1M) for 0.5h for activation, and then ultrasonically cleaned and dried with a large amount of deionized water. 1g 2-amino-terephthalic acid and 0.4g sodium hydroxide were dispersed in 100mL ethanol and ultrasonically treated for 0.5h to disperse evenly. 1.5mmol NiCl2·6H2O and 1.5mmol CoCl2·6H2O were added in sequence and ultrasonically treated again for 0.5h to completely dissolve in 200mL ethanol. Then, the mixed solution was oil bathed at 100℃ for 8h, and Ni1Co1-TPA was obtained after separation, washing and vacuum drying. Ni1Co1-TPA was further dispersed in an aqueous solution containing three metal salts of 1.5mmol FeCl3·6H2O, 1.5mmol CuCl2 and 1.5mmol RuCl3, and stirred at room temperature for 12h. After separation, washing and vacuum drying, a solid mixture powder FeCuRu@Ni1Co1-TPA was obtained. After that, 30 mg of the obtained precursor powder was weighed and dispersed in 1 mL of ethanol for ultrasonic dispersion for 0.5 h, and then 40 μL of Nafion was added and ultrasonic dispersion was performed for another 0.5 h to form a uniform dispersion. 100 μL of the dispersion was dropped on a piece of activated nickel foam (1×1 cm) and dried by infrared lamp irradiation to obtain a nickel foam coated with a metal precursor. The nickel foam coated with a metal precursor was heated to 2000°C in an argon atmosphere by Joule heating to obtain a FeCuRu@Ni1Co1-TPA high entropy alloy electrode.

[0056] Example 4

[0057] Pt / C electrode: Weigh 5 mg of Pt / C sample, place in 1 mL of ethanol solution, ultrasonically disperse at room temperature for 0.5 h, then add 40 μL of Nafion, and ultrasonically disperse for another 0.5 h to form a uniform dispersion. Drop 50 μL of the dispersion on the surface of an activated nickel foam (1×1 cm) (the pretreatment method of the nickel foam is the same as in Example 1), dry under infrared light, and obtain a Pt / C-loaded nickel foam electrode.

[0058] Example 5

[0059] RuO2 catalyst: Weigh 5 mg of RuO2 sample, place in 1 mL of ethanol solution, ultrasonically disperse at room temperature for 0.5 h, then add 40 μL of Nafion, and ultrasonically disperse for another 0.5 h to form a uniform dispersion. Drop 50 μL of the dispersion on the surface of an activated nickel foam (1×1 cm) (the pretreatment method of the nickel foam is the same as in Example 1), dry under infrared light, and obtain a RuO2-loaded nickel foam electrode.

[0060] Example 6

[0061] Nafion / NF catalyst: 40 μL Nafion was added dropwise on the surface of an activated nickel foam (1×1 cm) (the pretreatment method of the nickel foam was the same as in Example 1), and dried at room temperature to obtain a Nafion-loaded nickel foam electrode.

[0062] Experimental Example 7

[0063] like Figure 1 and Figure 2 As shown in the SEM and TEM images, the FeCuRu@Ni1Co1-TPA high entropy alloy powder presents a large number of regular nanoparticles.

[0064] The crystal structure of FeCuRu@Ni1Co1-TPA high entropy alloy was analyzed by XRD. Figure 3 ), XRD results show that the product obtained in this example is a high entropy alloy solid solution containing Fe, Co, Ni, Cu, and Ru.

[0065] Electrochemical measurements were performed in a typical three-electrode system, with a graphite rod as the counter electrode, a Hg / HgO electrode as the reference electrode, and the synthesized electrode material as the working electrode. Linear sweep voltammograms were used to evaluate the electrochemical performance at 1 mV s -1 Electrocatalytic hydrogen evolution performance at a scan rate of .

[0066] like Figure 4 As shown in Figure 2, the FeCuRu@Ni1Co1-TPA high entropy alloy electrode exhibits excellent hydrogen evolution catalytic performance under alkaline conditions, reaching 500 mA cm -2 The overpotential of the current density is only 120 mV. This value is significantly lower than that of Pt / C (357 mV) and Nafion / NF (412 mV), indicating that the formation of an alloy structure with uniform five metals is beneficial to improving the performance of HER.

[0067] Electrochemical measurements were performed in a typical three-electrode system, with a graphite rod as the counter electrode, a Hg / HgO electrode as the reference electrode, and the synthesized electrode material as the working electrode. Linear sweep voltammograms were used to evaluate the electrochemical performance at 1 mV s -1 Electrocatalytic oxygen evolution performance at a scan rate of .

[0068] like Figure 5 As shown in Figure 2, the FeCuRu@Ni1Co1-TPA high entropy alloy electrode exhibits excellent oxygen evolution catalytic performance under alkaline conditions, reaching 500 mA cm -2 The overpotential of the current density is only 350 mV. This value is significantly lower than that of RuO2 (620 mV) and Nafion / NF (636 mV), indicating that the formation of an alloy structure with uniform five metals is beneficial to improving the performance of OER.

[0069] Electrochemical measurements were performed in a typical three-electrode system, with a graphite rod as the counter electrode, a Hg / HgO electrode as the reference electrode, and the synthesized electrode material as the working electrode. Linear sweep voltammograms were used to evaluate the electrochemical performance at 1 mV s -1 Electrocatalytic hydrogen evolution performance at a scan rate of .

[0070] like Figure 6 As shown in Figure 2, the FeCuRu@Ni1Co1-TPA high entropy alloy electrode exhibits excellent hydrogen evolution catalytic performance under neutral conditions, reaching 50 mA cm -2 The overpotential of the current density is only 83 mV. This value is significantly lower than that of Pt / C (296 mV) and Nafion / NF (424 mV), indicating that the formation of an alloy structure with uniform five metals is beneficial to improving the performance of HER.

[0071] Electrochemical measurements were performed in a typical three-electrode system, with a graphite rod as the counter electrode, a Hg / HgO electrode as the reference electrode, and the synthesized electrode material as the working electrode. Linear sweep voltammograms were used to evaluate the electrochemical performance at 1 mV s -1 Electrocatalytic oxygen evolution performance at a scan rate of .

[0072] like Figure 7 As shown in Figure 2, the FeCuRu@Ni1Co1-TPA high entropy alloy electrode exhibits excellent oxygen evolution catalytic performance under neutral conditions, reaching 50 mA cm -2 The overpotential of the current density is only 280 mV. This value is significantly lower than that of RuO2 (600 mV) and Nafion / NF (740 mV), indicating that the formation of an alloy structure with uniform five metals is beneficial to improving the performance of OER.

[0073] With the outstanding performance in both OER and HER, the overall water splitting performance was tested in a two-electrode system with FeCuRu@Ni1Co1-TPA high entropy alloy electrodes as anode and cathode. Linear sweep voltammograms were used to evaluate the water splitting performance at 1 mV s -1 The FeCuRu@Ni1Co1-TPA(+)||FeCuRu@Ni1Co1-TPA(-) electrode only needs a potential of 1.58 V to reach 100 mA cm -2 Current density ( Figure 8 ), which is significantly lower than 1.94 V of Pt / C(+)||RuO2(-) electrode.

[0074] Linear sweep voltammograms were used to evaluate the voltammogram at 1 mV s in 1 M PBS solution.-1 The FeCuRu@Ni1Co1-TPA (+)||FeCuRu@Ni1Co1-TPA (-) electrode only needs a potential of 1.50 V to reach 10 mA cm -2 Current density ( Fig. 9 ), which is significantly lower than 1.94 V of Pt / C(+)||RuO2(-) electrode.

[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for rapidly synthesizing a self-supporting high entropy alloy nanobifunctional electrocatalyst by Joule heat, characterized in that: The following steps are involved: (1) Pretreatment of the self-supporting carrier: pretreatment of the nickel foam in acetone, ethanol, and hydrochloric acid; (2) Synthesis of high entropy alloy precursor: 2-aminoterephthalic acid, sodium hydroxide, and two metal chlorides of Co and Ni are uniformly dissolved in ethanol and heated for 2 to 10 hours. Ni1Co1-TPA is obtained after centrifugation and washing. (3) Further adsorption of metal salts: The above product Ni1Co1-TPA is further dispersed into an aqueous solution containing three metal salts of Fe, Cu and Ru, and stirred at room temperature for 2 to 12 hours; (4) Precursor washing and drying: The reactant obtained in step (3) is centrifuged, and the obtained product is washed three times with ethanol and deionized water respectively, and the solid mixture is placed in a vacuum drying oven for drying; (5) Preparation of self-supporting electrocatalyst: preparing the catalyst powder obtained in step (4) into a uniformly dispersed liquid droplet and applying it to the pretreated nickel foam described in step (1), and drying to obtain a nickel foam coated with a high entropy alloy precursor; (6) Joule heating of the electrocatalyst: The nickel foam coated with the high entropy alloy precursor described in step (5) is subjected to Joule heating in an argon atmosphere to obtain the desired sample FeCuRu@Ni1Co1-TPA.

2. The Joule heat rapid synthesis of bifunctional self-supporting high entropy alloy nanoparticle electrocatalyst according to claim 1, characterized in that: The bifunctional electrocatalyst is FeCuRu@Ni1Co1-TPA high entropy alloy nanoparticles.

3. The Joule heat rapid synthesis of bifunctional self-supporting high entropy alloy nanoparticle electrocatalyst according to claim 1, characterized in that: The specific steps of the pretreatment in step (1) are: immersing the nickel foam in acetone, ethanol, and hydrochloric acid (1M) in sequence for ultrasonic treatment for 0.5 to 1 hour, and then performing ultrasonic cleaning with deionized water for several times until it is neutral.

4. The Joule heat rapid synthesis of bifunctional self-supporting high entropy alloy nanoparticle electrocatalyst according to claim 1, characterized in that: In step (2), there is no special limitation on the specific types of Fe salt, Co salt, Ni salt, Cu salt and Ru salt. In the experiment, the Fe salt is FeCl3·6H2O, the Co salt is CoCl2·6H2O, the Ni salt is NiCl2·6H2O, the Cu salt is CuCl2 and the Ru salt is RuCl3.

5. The Joule heat rapid synthesis of bifunctional self-supporting high entropy alloy nanoparticle electrocatalyst according to claim 1, characterized in that: In step (2), the molar ratio of FeCl3·6H2O, CoCl2·6H2O, NiCl2·6H2O, CuCl2 and RuCl3 is: 0.5~2:0.5~2:0.5~2:0.5~2:0.5~2.

6. The Joule heat rapid synthesis of bifunctional self-supporting high entropy alloy nanoparticle electrocatalyst according to claim 1, characterized in that: In the mixed metal salt solution in step (2), the concentration of a single metal salt is 0.5 to 2 mmol.

7. The Joule heat rapid synthesis of bifunctional self-supporting high entropy alloy nanoparticle electrocatalyst according to claim 1, characterized in that: In step (5), Joule heating is performed to a temperature of 900 to 2500°C.

8. The bifunctional self-supporting high entropy alloy nanoparticle electrocatalyst according to claim 1, characterized in that: The catalyst is a bifunctional catalyst and can be used to catalyze water decomposition reactions.

Citation Information

Cited By

  • Preparation method and application of Al-doped CuO nanosheet electrocatalyst

    CN119824460A

  • NiFe / INF catalyst, preparation method and application

    CN119843320A

  • Hydrogen production catalyst as well as preparation method and application thereof

    CN120272954A

  • Hydrogen production catalyst, preparation method and application thereof

    CN120272954B